Encouraging Best Practice in Quantitative Management Research: An Incomplete List of Opportunities* - Echambadi, Raj; Campbell, Benjamin; Agarwal, Rajshree (Journal of Management Studies, 2006)
abstract The paper identifies some common problems encountered in quantitative methodology and provides information on current best practice to resolve these problems. We first discuss issues pertaining to variable measurement and concerns regarding the underlying relationships among variables. We then highlight several advances in estimation methodology that may circumvent issues encountered in common practice. Finally, we discuss approaches that move beyond existing research designs, including the development and use of datasets that embody linkages across levels of analysis, or combine qualitative and quantitative methods.